Good Governance in The Digital Age: Exploring The Impact of e-UNNAT in Kulgam District of Jammu and Kashmir - Muzamil Shafi; Singh, Manvendra (Journal of Neonatal Surgery, 2025)
The study examines the impact of e-UNNAT in promoting good governance in Kulgam District, Jammu and Kashmir. It highlights the role of e-governance in improving government services, particularly in terms of accessibility and efficiency. The concept of e-governance has emerged as a transformative tool in improving governance processes in the Union Territory of Jammu and Kashmir. In context to statistical analysis, people in the Kulgam district have witnessed the benefits in service delivery and transparency under the shadow of e-UNNAT; however, gaps in awareness and inclusivity remain. A noticeable gender imbalance and lack of outreach suggest the need for more effective communication. The findings align with the theoretical framework emphasizing the importance of ICT in governance but stress the need for continuous engagement, better infrastructure, and improved service delivery to maximize e-UNNAT's potential.